FUNDUSZ POMOCY POKRZYWDZONYM ORAZ POMOCY POSTPENITENCJARNEJ – O NOWEJ INSTYTUCJI PRAWA KARNEGO WYKONAWCZEGO KRYTYCZNIE - Bieńkowska, Ewa (Zeszyty Prawnicze, 2016)
CRIME VICTIMS AND THE POLISH POSTPENITENTIARY ASSISTANCE FUND: A CRITICAL ASSESSMENT OF A NEW INSTITUTION FOR EXECUTIVE PENAL LAW Summary The paper describes and analyses the regulation of a Fund which has been in operation since January 1st, 2012. The idea behind the Fund was to establish a centralised system for the management and fair distribution of financial resources allocated to assist crime victims and persons discharged from penitentiary institutions. Paradoxically, however, the two parts of the Fund come from separate sources. In the author’s opinion it is completely unacceptable to incorporate a regulation concerning victims of crime in the executive code of penal law, which regulates the execution of penalties imposed on perpetrators of crime and is not concerned with crime victims at all. The analysis of the details of the Fund shows that the legislator’s main intention was to find financial justification for his own activity and to create a means of control over non-governmental organisations assisting crime victims.